2020
DOI: 10.1177/1053825920952086
|View full text |Cite
|
Sign up to set email alerts
|

Contemplative Pedagogy: Fostering Transformative Learning in a Critical Service Learning Course

Abstract: Background: Research demonstrating the positive outcomes of service learning among university students is robust and some describe the impact as transformative. Purpose: To help me better understand how I can support transformative learning in my classroom, this study explored how an intergenerational critical service learning project fostered change among student participants. Methodology/Approach: Data consisted of reflection journals collected over 6 years from 228 students who participated in a course-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…However, they would turn to be happy at the end of SL under the community/ institution partner's assistances or when the served gave them positive feedback. In other words, as Gardner (2021) stressed "how" SL does is less explored in research, rather than knowing "what" emotions are, our study argues, for course instructors, "how" students' emotions occur and "what" are students' emotion processes of SL are suggested to be considered while conducting a SL course since some research found students' academic satisfaction and achievement are connected to fewer bad emotional experiences and more good emotional experiences (Kleine, 2005;Lee, & Chei, 2020).…”
Section: Discussionmentioning
confidence: 90%
“…However, they would turn to be happy at the end of SL under the community/ institution partner's assistances or when the served gave them positive feedback. In other words, as Gardner (2021) stressed "how" SL does is less explored in research, rather than knowing "what" emotions are, our study argues, for course instructors, "how" students' emotions occur and "what" are students' emotion processes of SL are suggested to be considered while conducting a SL course since some research found students' academic satisfaction and achievement are connected to fewer bad emotional experiences and more good emotional experiences (Kleine, 2005;Lee, & Chei, 2020).…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, the word kepedulian (concern) resonates with the contemplative pedagogy advocated by Gardner (2020), who emphasizes the importance of fostering a learning environment that encourages care for self and others, promoting transformative learning experiences. The practice of sembahyang within the educational framework at Pasastrian Kusalamitra aligns with the spiritual nurturing highlighted in the work of Hyde (2016), which discusses the practical expression of educational values such as hospitality and spiritual care in schools.…”
Section: Diagram 1 Visualizing Ethics Word Cloud Analysis Of Buddhist...mentioning
confidence: 99%
“…Therefore, SL pedagogy can be used to explore the extent to which it can help to unearth learners' shortcomings in reading and enhance their reading skills. As a result, SL can assist students in learning lecture material by providing them with real-world experiences that deepen their understanding in the promotion of critical thinking and a sense of responsibility for their education (Gardner, 2021). Hence, Hou (2022) posits that SL allows students to apply theoretical concepts from lectures to real-world experiences.…”
Section: Introductionmentioning
confidence: 99%